A chemical study of the coloring matters of Curcuma longa Linne (Family Zingiberaceae) - Talusan, Elizabeth G.; Castillo, Amorita V.; Concepcion. Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1979.)
Orange-yellow crystalline powder was isolated from the air-dried, powdered rhizomes of Curcuma longa L. m.p. 178-183. Thin layer chromatography of the benzene extract gave three major components and to minor components. The first and second spots, having Rf values of 0.16 and 0.28 respectively, are closely related to curcumin, the major coloring matter of Curcuma longa L. Spectrophotometric analyses were also made.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, March 1979.
Keywords: Zingiberaceae; Turmeric; Dilau